Terminal Value Problem for Implicit Katugampola Fractional Differential Equations in b-Metric Spaces. (3rd May 2021) - Krim, Salim; Abbas, Saïd; Benchohra, Mouffak; Karapinar, Erdal
Abstract : This manuscript deals with a class of Katugampola implicit fractional differential equations in b -metric spaces. The results are based on the α − φ -Geraghty type contraction and the fixed point theory. We express an illustrative example.